Advances in the solution of geotechnical boundary-value problems. (October 2021) - Salgado, Rodrigo; Bisht, Vibhav
Abstract: Seminal work done at the University of Newcastle on constitutive model integration, limit analysis, finite element analysis, and large deformation analyses have been instrumental in the development of strategies for the solution of the boundary-value problems of geomechanics. In this study, we present the results of analyses performed to demonstrate the usefulness of these contributions. In the first set of analyses, the accuracy and efficiency of time integration schemes is evaluated by simulating the response of Toyoura sand to undrained simple shear loading. In the second set of analyses, finite element limit analysis results are used to validate solutions obtained for certain boundary-value problems using the material point method (MPM). In the third set of analyses, a coupled MPM formulation is used to predict the bearing capacity of a strip footing under dynamic loads. The MPM results are compared against the results obtained using a coupled arbitrary Lagrangian-Eulerian approach. In the final set of analyses, the MPM is used to simulate penetration of a flat-tip and a conical-tip penetrometer into Ottawa 20–30 sand. The simulations, which closely match the experimental results, show that the flat-tip penetrometer mobilizes higher resistances than the conical-tip penetrometer throughout the penetration process.